2003
DOI: 10.1002/asna.200385103
|View full text |Cite
|
Sign up to set email alerts
|

Full Three Dimensional Orbits For Multiple Stars on Close Approaches to the Central Supermassive Black Hole

Abstract: With the advent of adaptive optics on the W. M. Keck 10m telescope, two significant steps forward have been taken in building the case for a supermassive black hole at the center of the Milky Way and understanding the black hole's effect on its environment. Using adaptive optics and speckle imaging to study the motions of stars in the plane of sky with ±∼2 mas precision over the past 7 years, we have obtained the first simultaneous orbital solution for multiple stars. Among the included stars, three are newly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 29 publications
1
44
0
Order By: Relevance
“…We shall first consider the case of Sgr A* for which the mass of the SMBH is estimated to be M BH ≃ 3.5 × 10 6 M ⊙ (Schödel et al 2002; Ghez et al 2003). For this particular example, we shall accept that Σ * = 0.001 Σ and that the initial masses of protostars are M * = 0.1 M ⊙ .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We shall first consider the case of Sgr A* for which the mass of the SMBH is estimated to be M BH ≃ 3.5 × 10 6 M ⊙ (Schödel et al 2002; Ghez et al 2003). For this particular example, we shall accept that Σ * = 0.001 Σ and that the initial masses of protostars are M * = 0.1 M ⊙ .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In 2002, Munyaneza & Viollier 71 showed that the then existing stellar motion data could only be fit by a restricted range of parameter space for a supermassive black hole, but could be easily fit by Fermion ball models. Subsequent observations of stellar orbits 38,39,40 showed that the supermassive black hole predictions were indeed met, and that the stars moved with speeds greater than allowed by their Fermion ball model. We note that the density limit employed in this section was the one obtained only from the orbits of stars.…”
Section: Excluding Alternatives To a Smbhmentioning
confidence: 99%
“…While the first Keplerian orbital elements of the S2's orbit could be derived from the pre-periapse data, the situation improved significantly after the periapse passage of S2 in 2002. NIR adaptive optics (AO) imaging allowed the derivation of detailed Keplerian orbital elements (Schödel et al 2002;Ghez et al 2003). NIR spectroscopy resulted in radial velocities, and hence in a determination of the mass and the distance to the GC derived from the orbital data (R 0 ; Ghez et al 2003Ghez et al , 2005Eisenhauer et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…NIR adaptive optics (AO) imaging allowed the derivation of detailed Keplerian orbital elements (Schödel et al 2002;Ghez et al 2003). NIR spectroscopy resulted in radial velocities, and hence in a determination of the mass and the distance to the GC derived from the orbital data (R 0 ; Ghez et al 2003Ghez et al , 2005Eisenhauer et al 2003). These results could be improved using other high-velocity Sstars in the vicinity of Sgr A* (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation